Appropriate Use of Transesophageal Echocardiogram for Infective Endocarditis: A Single Center Experience. (23rd October 2019) - Singh, Robby; Naidu, Moumita; Bader, Yousef; Freeman, David; Zughaib, Marcel
Abstract : Background . Transesophageal echocardiogram (TEE) is a valuable tool in healthcare today with its ease of use, ability to visualize important structures not seen on transthoracic echocardiogram (TTE), and the relatively lower cost of TEE, high yield, and no significant radiation exposure. The American Society of Echocardiography (ASE) has developed an appropriate use criteria for use of TTE and TEE, which outline various scenarios where a TEE is indicated as an initial diagnostic testing modality and when it is useful as an adjunctive test in hopes of decreasing inappropriate use. Using these criteria as a guide, we devised a quality assessment study to investigate how well TEEs performed at our institution fit the appropriate use criteria specifically for the diagnostic workup of infective endocarditis. Methods . A retrospective chart review was performed for all TEEs performed in 2017 with the indication of endocarditis. Baseline patient characteristics, presence of bacteremia, and the quality of the TTE preceding the TEE were noted, as well as whether a vegetation, abscess, or perforation was visualized. We also determined if there was a cardiology consultation placed prior to TEE and if the patient had met the definition for endocarditis as defined by the Duke criteria. Finally, we made note of the TEE findings and assessed whether the TEE met appropriate use criteria developed by the American Society of Echocardiography. Results . A total of 50 patients who underwent TEE with the indication of "endocarditis" were identified. 36% of the TTEs prior to the TEE were rated as good quality, 40% as adequate, 4% as fair, 4% as suboptimal, 12% as technically difficult, and 4% were not rated. Vegetations were visualized on 12% of TTEs, 6% of patients had a prosthetic valve, and 6% had a cardiac device. In 20% of the cases, there was no cardiology consultation prior to the TEE and in 20% of the cases, there was no documented bacteremia. 26% of patients met the Duke criteria for endocarditis prior to TEE. Only 36% of TEEs revealed evidence of infection and of the patients with no evidence of infection, only 38% met appropriate use criteria. Overall, only 56% of patients met appropriate use criteria for TEE. Conclusion . Transesophageal echocardiography is a valuable tool in a modern physician's arsenal for managing a variety of diseases and conditions. However, the procedure is not without associated risks and its ease of use and widespread adoption has led to frequent questionable appropriateness of use of the test. Only 56% of the TEEs performed in our analysis met appropriate use. More awareness and education is needed for the appropriate use criteria for transesophageal echocardiography as outlined by the ASE to help reduce patient exposure to procedure related complications and to decrease medical costs on unnecessary procedures.